Evaluation of River Basin Councils in Kazakhstan: the case of Aspara River - Zhalgas, Zhassulan; Alshagirov, Olzhas (Nazarbayev University Graduate School of Public Policy, 2019)
In the 21st century, there are many challenges with water resources in the world. To battle these challenges, Kazakhstan introduced the hydrographic (river) basin management approach in 2004 by establishing River Basin Organisations (RBOs) to coordinate water uses on a basin level. In order to engage local stakeholders, the River Basin Councils (RBCs) were developed on the national level; the National Policy Dialogues (NPDs) on water issues were launched, as well. As a result, the water management process became more inclusive, participatory and responsive....